Natural Flavonoids for the Amelioration of Acetaminophen-Induced Hepatotoxicity: A Systems Pharmacology-Based Study - Echeverria-Morgado, J (Springer Science and Business Media Deutschland GmbH, 2024)
Natural flavonoids have been promising in protecting against liver injuries induced by acetaminophen overdose, the leading cause of drug-induced hepatotoxicity. The present research was focused on an integrative approach to shed light on the currently unclear targeted pathways and possible molecular mechanisms involved in such alleviating effects. This study aimed to apply systems pharmacogenomics to identify the proteins and pathways targeted by flavonoids that ameliorate acetaminophen-induced hepatotoxicity (AIH), as well as to comparatively examine the potential utility of both targets and phytoligands for treating AIH. The overall research plan involves evidence-based compiling of AIH-protecting flavonoids, systems-based target screening, and target–flavonoid interaction studies by molecular modeling. Overlapping elements between predicted compounds’ targets and disease-related targets were used to build an expanded protein–protein interaction (PPI) network to identify the significant pathways involved in the hepatoprotective effects of the flavonoids. Compound-target-pathway data integration provided a final set of targets and ligands, which were used for molecular interaction studies by using molecular docking. Prostaglandin-endoperoxide synthase 2 (PTGS2) was a hub in the PPI network, a central element in the compound-target-pathway network, the best target for chrysin, and the top receptor for oroxyloside. Monoamine oxidase A (MAOA) was a commonly predicted target, a central element in the integrative network, and the best target for seven out of the ten flavonoids. PTGS2-oroxyloside, MAOA-quercetin, CFTR-oroxyloside, and MAOA-naringenin were identified as the most capable complexes of flavonoid nutraceuticals with AIH therapeutical targets to be further studied for treating AIH. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.